Prosedur Pemeriksaan MRI Cruris dengan Kontras pada Kasus Tumor - Ambarwati, Seli; Sulaksono, Nanang; Jannah, Marichatul (Poltekkes Kemenkes Semarang, 2025)
Background: This study examines the MRI Cruris contrast examination procedure for tumor cases at Dr. Moewardi Hospital. The hospital's MRI protocol includes sequences such as 3-plane localizer, Sag T1, Sag T2, Ax T1, Ax T2 STIR, Coronal T1, Coronal PD FS, Coronal T2* MERGE, 3D Coronal TRICKS, and post-contrast sequences Sag T1+C, Coronal T1+C, and Ax T1+C. The study aims to analyze the MRI Cruris contrast procedure, the rationale for using 5 ml contrast, and the importance of the Coronal 3D TRICKS sequence.Methods: A qualitative research method with a case study approach was used, involving observation, interviews, and documentation. The data was analyzed and presented in quotations to conclude.Result and Discussion: The MRI procedure begins with patient preparation, including laboratory tests for urea and creatinine levels, fasting for 4–6 hours, and filling out informed consent. Patients are positioned supine with feet first, and an air coil is placed on the leg. The use of 5 ml contrast enhances image quality, improves tumor detection, evaluates blood vessels, shows lesions, and determines tumor location and spread. The Coronal 3D TRICKS sequence provides clear MRA angiography, enabling better visualization of feeding arteries and rapid imaging of major blood vessels within 10 seconds.Conclusion: In conclusion, the MRI Cruris contrast protocol at Dr. Moewardi Hospital ensures high-quality imaging for tumor detection and diagnosis. The 5 ml contrast dose effectively enhances MRI images, and the Coronal 3D TRICKS sequence plays a crucial role in evaluating vascular structures.